Experimental Detection and Simulation of Terahertz Spectra of Aqueous L-Arginine - Lei Hou; Junnan Wang; Haiqing Wang; Lei Yang; Wei Shi (Biosensors, 2022)
Terahertz (THz) wave is a good candidate for biological sample detection, because vibration and rotation energy levels of biomolecule are in THz band. However, the strong absorption of THz wave by water in biological samples hinders its development. In this paper, a method for direct detection of THz absorption spectra of L-arginine suspension was proposed by using a strong field THz radiation source combined with a polyethylene cell with micrometer thickness in a THz time-domain spectroscopy system. And the THz absorption spectrum of L-arginine solution was simulated by the density functional theory and the simulation result is in good agreement with the experimental results. Finally, the types of chemical bond interaction that cause the absorption peak are identified based on the experimental and simulation results. This work paves a way to investigate the THz absorption spectra and intramolecular interactions of aqueous biological samples.